Stimulation of mitochondrial oxidative capacity in white fat independent of UCP1: a key to lean phenotype - Flachs, Pavel; Rossmeisl, Martin; Kuda, Ondrej; Kopecky, Jan (Biochimica et biophysica acta, 2013)
We are facing a revival of the strategy to counteract obesity and associated metabolic disorders by inducing thermogenesis mediated by mitochondrial uncoupling protein-1 (UCP1). Thus, the main focus is on the adaptive non-shivering thermogenesis occurring both in the typical depots of brown adipose tissue (BAT) and in UCP1-containing cells that could be induced in white adipose tissue (WAT). Because contribution of WAT to resting metabolic rate is relatively small, the possibility to reduce adiposity by enhancing energy expenditure in classical white adipocytes is largely neglected. However, several pieces of evidence support a notion that induction of energy expenditure based on oxidation of fatty acids (FA) in WAT may be beneficial for health, namely: (i) studies in both humans and rodents document negative association between oxidative capacity of mitochondria in WAT and obesity; (ii) pharmacological activation of AMPK in rats as well as cold-acclimation of UCP1-ablated mice results in obesity resistance associated with increased oxidative capacity in WAT; and (iii) combined intervention using long-chain n-3 polyunsaturated FA (omega 3) and mild calorie restriction exerted synergism in the prevention of obesity in mice fed a high-fat diet; this was associated with strong hypolipidemic and insulin-sensitizing effects, as well as prevention of inflammation, and synergistic induction of mitochondrial oxidative phosphorylation (OXPHOS) and FA oxidation, specifically in epididymal WAT. Importantly, these changes occurred without induction of UCP1 and suggested the involvement of: (i) futile substrate cycle in white adipocytes, which is based on lipolysis of intracellular triacylglycerols and re-esterification of FA, in association with the induction of mitochondrial OXPHOS capacity, β-oxidation, and energy expenditure; (ii) endogenous lipid mediators (namely endocannabinoids, eicosanoids, prostanoids, resolvins, and protectins) and their cognate receptors; and (iii) AMP-activated protein kinase in WAT. Quantitatively, the strong induction of FA oxidation in WAT in response to the combined intervention is similar to that observed in the transgenic mice rendered resistant to obesity by ectopic expression of UCP1 in WAT. The induction of UCP1-independent FA oxidation and energy expenditure in WAT in response to the above physiological stimuli could underlie the amelioration of obesity and low-grade WAT inflammation, and it could reduce the release of FA from adipose tissue and counteract harmful consequences of lipid accumulation in other tissues. In this respect, new combination treatments may be designed using naturally occurring micronutrients (e.g. omega 3), reduced calorie intake or pharmaceuticals, exerting synergism in the induction of the mitochondrial OXPHOS capacity and stimulation of lipid catabolism in white adipocytes, and improving metabolic flexibility of WAT. The role of mutual interactions between adipocytes and immune cells contained in WAT in tissue metabolism should be better characterised. This article is part of a Special Issue entitled Brown and White Fat: From Signaling to Disease.
Keywords: Animals; Phenotype; oxidační stres; Adipose Tissue, White; Mitochondria; Oxidative Stress; energetický metabolismus; Oxidative Phosphorylation; lidé; Adipocytes; Lipid Metabolism; Mice; Energy Metabolism; signální transdukce; mitochondriální proteiny; myši; Signal Transduction; metabolismus lipidů; mitochondrie; Humans; iontové kanály; oxidativní fosforylace; Ion Channels; krysa rodu Rattus; fenotyp; zvířata; Mitochondrial Proteins; bílá tuková tkáň; Rats; tukové buňky